Managing Productive Waqf in Indonesia: Professionalism, Fundraising, and Distribution - Adhma Khoiri, Fatwa; Anggi Aulinna Khofifah (Tebuireng: Journal of Islamic Studies and Society, 2026)
This article examines the influence of internal factors, including professional trustees, management, fundraising, and distribution, on the optimization of productive waqf in the Indonesian Waqf Land Institution and the Indonesian Waqf Agency. Using an entrepreneurship theory approach, this study seeks to explain how these internal factors play a role in optimizing the management of productive waqf, both individually and collectively, in Indonesia. The primary focus of this study is to evaluate the contribution of each factor toward achieving the objectives of productive waqf, which impact the social and economic well-being of the community. This study employs a quantitative method using a survey conducted via an online questionnaire. Data collected from respondents were analyzed using multiple linear regression processed with SPSS 26 software. This approach enables the study to gain a comprehensive understanding of the relationship between internal factors and the optimization of productive waqf. The independent variables in this study include professional trustees, management, collection, and distribution, while the dependent variable is the level of productive waqf optimization. The results indicate that the variables of professional trustees and collection have a significant negative influence on the optimization of productive waqf. Conversely, the management and distribution variables show a significant positive influence. Simultaneously, the internal factors studied exert a significant positive influence on the optimization of productive waqf. These findings make an important contribution to the development of productive waqf management strategies, where improving effective management and distribution can be a top priority in supporting the optimal utilization of waqf for the public good.